Total Just-in-Time: An Empirical Study of Interelationship toward Operational Performance of Manufacturing Entities - Natasya Lia Alfi; Pudjo Sugito; Ririn Sudarwati (Business Management Research, 2025)
This study aims to analyze the effect of Total Just In Time (which consists of Just In Time Production, Just In Time Purchasing, and Just In Time Selling) on Operational Performance. The sample used was 73 employees in the production department at PG Kebon Agung Malang from a total population of 220 employees, sampling using the simple random sampling method and for sampling using the Slovin formula approach. Data were analyzed descriptively and inferentially using validity and reliability tests, multiple linear regression, as well as t-test and F-test. The results showed that the implementation of Total Just In Time as a whole had a positive and significant effect on Operational Performance. Partially, the three Just In Time variables also had a significant effect, with Just In Time Purchasing being the variable that had the most dominant effect. This shows that timely, efficient, and planned management of raw material purchases is an important factor in increasing the efficiency of the production process, reducing waste, and maintaining product quality. These findings support previous theories and research regarding the strategic role of the Just In Time system in supporting the improvement of the company's operational performance.